An integrated analysis to predict micro‐RNAs targeting both stemness and metastasis in human gastric cancer. Issue 2 (31st August 2020) - Azimi, Mahnaz; Totonchi, Mehdi; Rahimi, Mahsa; Firouzi, Javad; Sahranavard, Parisa; Emami Razavi, Amirnader; Memari, Fereidoon; Kamali, Fatemeh; Ebrahimi, Marzieh
Abstract: Background and Aim: Cancer stem cells (CSCs), a subpopulation of tumor cells, assess the capacity of self‐renewal, metastasis, and therapeutic resistance. Regulation of CSCs and their epithelial to mesenchymal transition (EMT) potential is one of the promising strategies to eliminate cancer or to inhibit metastasis. Micro‐RNAs (miRNAs) as regulators of several cell properties, such as self‐renewal, metastasis, and resistance to the drug, could be proper targets in cancer diagnosis and therapy. The aim of the present study is to select common miRNAs targeting both self‐renewal and metastasis in gastric cancer. Methods: Stemness‐related and EMT‐related genes were selected by literature mining. The common miRNAs targeting genes were chosen using different databases and r programming language. The expression pattern of selected miRNAs and genes was evaluated in gastrospheres—as a gastric CSC model—and gastric tumor biopsies. Results: Based on the integrated analysis, six miRNAs common to both stemness and metastasis were identified. miR‐200c‐3p and miR‐520c‐3p overexpressed in MKN‐45 gastrospheres and grade III tumors. In AGS spheres, however, miR‐520c‐3p and miR‐200c‐3p upregulation and miR‐34a‐5p downregulation were similar to grade II tumors. Interestingly, miR‐200c‐3p and miR‐520c‐3p indicated a positive correlation with OCT4 and NOTCH1 expression in grade III tumors and MKN‐45 spheres. Protein–protein network revealed that the EMT acquisition can be induced by stemness activation through intermediated core‐regulatory genes, including CTNNB1, CTNND1, MAML1, KAT2A, and MAML3 . Conclusion: The upregulation of mir‐200c‐3p and mir‐520c‐3p could effect on stemness and metastasis in gastric cancer as well as gastric CSCs. Therefore, they can be used as diagnosis and prognostic factors.